Actual procedures of diagnostics and treatments of crural venous ulcer in specialized German praxis and clinics - Reich-Schupke, S.; Altmeyer, P.; Stücker, M. (Phlebologie, 2009)
Background: To evaluate the implementation of the guidelines of the German Society of Phlebology for venous crural ulcer a survey was conducted during the annual meeting of the German Society of Phlebology 2008 in Bochum. Methods: All 719 medical participants got an anonymized questionnaire asking for supply of crural ulcer in their institution. Results: The recurrent 66 questionnaires (9.2%) were filled by colleagues from practice or hospital, mostly surgeons, dermatologists, phlebologists and vascular surgeons. As basic diagnostics vein doppler (56.1%), duplex (75.8%) or measurement of brachial-ankleindex (83.3%) were performed. Compression therapy is used in all institutions. Mainly used wound dressings are polyurethane foam dressings, alginates, hydrocolloids and silver dressings. About 2/3 conduct surgical therapy of ulcers. Conclusion: Supply of ulcus cruris by the participants of the annual meeting of the DGP corresponds mainly, but not in all aspects to the guidelines. Further efforts for a spread of the guidelines are necessary.
Keywords: Ulcus cruris; supply; Germany; guidelines